Windows 8 Apps Revealed Using XAML and C# Using XAML and C# - Freeman, Adam. (Apress : Imprint: Apress, 2012)
This 88-page primer unveils the key features of Microsoft's eagerly anticipated Windows 8 operating system. Windows 8 contains Microsoft's revolutionary new application framework for building dynamic and responsive touch-enabled applications that target both desktops and mobile devices. Experienced author Adam Freeman invites you to take a crash course in Windows 8 development. Using the open standards of XAML and C# he ensures you understand the changes that are being made to Windows development practices and puts you on the right course to creating innovative and elegant applications for this latest evolution of the world’s most successful operating system.